2010
DOI: 10.1093/qjmed/hcq056
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing 'legal highs' on the Internet--is there consistency in what you get?

Abstract: Whilst there was no variation in the composition of most legal highs supplied over 6 month, there was significant variation in the piperazine or cathinone content of one quarter of the products. This variation could be of clinical significance as the cathinone and piperazine products can be associated with significant toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(121 citation statements)
references
References 9 publications
1
119
0
1
Order By: Relevance
“…It is possible that the Internet suppliers themselves may be confused as to which substance they are intending to sell, since in some user discussion fora, there appears to be confusion between 4-methylaminorex and 4,4′-dimethylaminorex [13,14]. In addition, there are numerous studies that have demonstrated that the contents of NPS products purchased from the Internet, high street headshops or street-level drug dealers are variable and the actual contents may not reflect the stated contents [15][16][17][18][19][20]. The main limitation of the Internet snapshot methodology is that the products are not purchased and analysed; therefore, it is not possible to be certain of the actual contents of the products being sold.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the Internet suppliers themselves may be confused as to which substance they are intending to sell, since in some user discussion fora, there appears to be confusion between 4-methylaminorex and 4,4′-dimethylaminorex [13,14]. In addition, there are numerous studies that have demonstrated that the contents of NPS products purchased from the Internet, high street headshops or street-level drug dealers are variable and the actual contents may not reflect the stated contents [15][16][17][18][19][20]. The main limitation of the Internet snapshot methodology is that the products are not purchased and analysed; therefore, it is not possible to be certain of the actual contents of the products being sold.…”
Section: Discussionmentioning
confidence: 99%
“…Consistency of ingredients is also unpredictable. "Legal high" brand name products, analyzed over a 6-month period, changed ingredients in 25% of the samples [24].…”
Section: Contentsmentioning
confidence: 99%
“…Selfreported doses range from a few milligrams to over 1 g of powder [6,17,25,27]. Users cannot be certain of the actual contents or the purity of the drug, therefore actual exposure is highly variable [22,24].…”
Section: Patterns Of Usementioning
confidence: 99%
“…However, in a patient population with sympathomimetic toxicity, it cannot be reliably distinguished whether caffeine contributed to the clinical manifestations of sympathomimetic toxicity or not. Furthermore, there are several reports of novel psychoactive substances, specifically those claiming to be synthetic cathinones, that were analyzed and found to contain significant concentrations of caffeine with some containing only caffeine [11][12][13].…”
Section: Limitationsmentioning
confidence: 99%